The Influence of Digital Marketing and Online Customer Reviews on Purchase Decisions in Lerep Culinary Market (Case Study on Visitors to Lerep Culinary Market, Semarang Regency) - lisnawati, anik; Kurniawan, Bayu; Meiriyanti, Rita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to measure the influence of Digital Marketing variables and Online Customer Review variables on Purchase Decisions mediated by Buying Interest in Lerep Culinary Market. The research method used to analyze the data is SPSS 23. The specified sample was 100 using the non-probability sampling method. Sampling that must have criteria, thus can use the purposhive sampling technique. The results of the data analysis were obtained from the T test that digital marketing has a significant positive effect on purchase decisions. Online customer reviews have a significant positive effect on decisions. In the F test, digital marketing and online customer reviews simultaneously had a positive and significant effect on purchase decisions.